2010
DOI: 10.2337/dc09-1830
|View full text |Cite
|
Sign up to set email alerts
|

MD-Logic Artificial Pancreas System

Abstract: OBJECTIVECurrent state-of-the-art artificial pancreas systems are either based on traditional linear control theory or rely on mathematical models of glucose-insulin dynamics. Blood glucose control using these methods is limited due to the complexity of the biological system. The aim of this study was to describe the principles and clinical performance of the novel MD-Logic Artificial Pancreas (MDLAP) System.RESEARCH DESIGN AND METHODSThe MDLAP applies fuzzy logic theory to imitate lines of reasoning of diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
159
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(165 citation statements)
references
References 14 publications
0
159
0
4
Order By: Relevance
“…Between 2008 and 2011, promising results from inpatient closed-loop control studies were reported by several groups. [40][41][42][43][44][45] The results from these investigations were summarized in a 2011 review of the artificial pancreas field, 46 pointing out the superiority of closed-loop control over insulin pump therapy in terms of (1) increased time within target glucose range, (2) reduced incidence of hypoglycemia, and (3) better overnight control. Subsequent studies confirmed these findings in outpatient setting, 47 at diabetes camps for children, 48 and at patients' homes.…”
Section: Utility Of Cgm Informationmentioning
confidence: 99%
“…Between 2008 and 2011, promising results from inpatient closed-loop control studies were reported by several groups. [40][41][42][43][44][45] The results from these investigations were summarized in a 2011 review of the artificial pancreas field, 46 pointing out the superiority of closed-loop control over insulin pump therapy in terms of (1) increased time within target glucose range, (2) reduced incidence of hypoglycemia, and (3) better overnight control. Subsequent studies confirmed these findings in outpatient setting, 47 at diabetes camps for children, 48 and at patients' homes.…”
Section: Utility Of Cgm Informationmentioning
confidence: 99%
“…During the closed-loop insulin delivery, the use of the pump was uninterrupted; the device was applied from 15:00 h on the day of the exercise to 13:00 h on the next day, and exercise was not announced to the closed-loop algorithm. The closed-loop algorithm (Glucositter; DreaMed Diabetes, Petah Tikva, Israel) used a modified vendor-supplied communication module application programming interface (API) to retrieve glucose/insulin data from the MiniMed Paradigm Veo pump and set insulin treatment according to a fuzzy-logicbased algorithm [21]. The software version 01.05.02 operated on a commercial laptop/tablet computer (ThinkPad T450s; Lenovo, Beijing, China), which had a physical connection to a communication dongle (provided by the manufacturer of the insulin pump).…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Between 2008 and 2012, promising results from inpatient CLC studies were reported by several groups. [3][4][5][6][7][8] A summary can be found in a 2011 review of the artificial pancreas field, pointing out the superiority of CLC over insulin pump therapy in terms of (1) increased time within target glucose range, (2) reduced incidence of hypoglycemia, and (3) better overnight control. 9 The transition of CLC to a wearable outpatient system began in 2012 with the introduction of the Diabetes Assistant (DiAs)-the first wearable CLC system using a smartphone as a computational platform for its control algorithm.…”
mentioning
confidence: 99%